Analisis Implementasi Rekam Medis Elektronik pada Klaster Pelayanan Kesehatan Ibu dan Anak - Nikmah Ayu Ramadhani Amir; Kholifah Hasnah (Universitas Batanghari Jambi, 2026)
The purpose of this study was to determine the implementation of electronic medical records in the maternal and child health service cluster at Puskesmas Pucangsawit Surakarta. This study used a qualitative descriptive research design by interviewing the coordinating midwife, PMIK staff, and health counseling staff as well as IT staff. The results showed that Puskesmas Pucangsawit has created its own digital medical record called E-Puskesmas which can meet user needs for external reporting and Puskesmas accreditation requirements. Interestingly, E-Puskesmas can be directly synchronized with SIMPUS, the official EMR platform provided by the Surakarta Health Office. The SWOT analysis results show that the strengths are the availability of an E-Puskesmas system that meets the needs of staff. The implementation of usernames, passwords, and PINs for each staff and management support in the implementation of electronic medical records.